2020
DOI: 10.1007/s41019-020-00147-9
|View full text |Cite
|
Sign up to set email alerts
|

How Good Are Modern Spatial Libraries?

Abstract: Many applications today like Uber, Yelp, Tinder, etc. rely on spatial data or locations from its users. These applications and services either build their own spatial data management systems or rely on existing solutions. JTS Topology Suite (JTS), its C++ port GEOS, Google S2, ESRI Geometry API, and Java Spatial Index (JSI) are some of the spatial processing libraries that these systems build upon. These applications and services depend on indexing capabilities available in these libraries for high-performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…An example is the PostGIS 8 , a PostgreSQL extension that employs the spatial libraries GEOS and GDAL. There are few studies that compare existing spatial libraries, such as the work in [Pandey et al 2020] that conducts experiments to analyze the performance of spatial libraries when executing spatial queries by using spatial index structures. However, a study that compares the support for spatial approximations is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the PostGIS 8 , a PostgreSQL extension that employs the spatial libraries GEOS and GDAL. There are few studies that compare existing spatial libraries, such as the work in [Pandey et al 2020] that conducts experiments to analyze the performance of spatial libraries when executing spatial queries by using spatial index structures. However, a study that compares the support for spatial approximations is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Main-memory servers: Common spatial libraries are limited to in-memory processing and thus require large main-memory servers to handle big data sets. We selected the Google S2 geometry library [17] as a baseline for the performance on large-memory servers, since a recent study reported that it has the most consistent performance across query classes [32]. Furthermore, it is optimized for spherical geometry, and is thus suitable to handle the data sets used in this evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Pandey et al [31] presented a detailed experimental evaluation of the state-of-the-art cluster-based spatial analytics systems. Pandey et al [32] also evaluated common spatial libraries. As we discussed, these approaches are effective but out of reach for many analysts.…”
Section: Related Workmentioning
confidence: 99%
“…Even libraries and packages of Python or R have also utilized the GEOS library for modeling spatial data. Recently, researchers have also proposed benchmarks [188,281] for computational geometry libraries used in data processing systems for spatial data exploration.…”
Section: Programming and Software Tools For Spatio-temporal Analysismentioning
confidence: 99%